Information Anxiety: A Phenomenon Experienced by Final Year Students During the Preparation of Their Thesis - Riftianti, Salsabila Dinda; Heriyanto, Heriyanto; Prasetyawan, Yanuar Yoga (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2024)
Background: Information anxiety is a topic of interdisciplinary study. Although it has been widely studied by researchers in the field of library and information science, several other fields such as education, business and economics also examine a person's information anxiety. However, this topic seems to have disappeared from scientific discussion, especially in scientific journals.Objective: This research tries to bring back the topic of information anxiety within the scope of Library and Information Science, especially in the context of education in higher education.Methods: The population in this study were final year students of one faculty at Diponegoro University class of 2018 with a population of 730 students and a sample size of 251 samples calculated using the Isaac and Michael formula with a significance level of 5%.Results: The results of the analysis show that students feel anxious when they cannot access the information, they need even though they know the location of the information. In other words, they experience anxiety when they know the location of information, but experience limited access in obtaining the information needed to support their thesis.Conclusion: The study reveals that students' information anxiety when writing a thesis is more influenced by limited access to information than by the abundance of information.